Relasi Interpersonal Amerika Serikat, China, dan Uni Eropa dalam Ekonomi dan Keamanan - Adikara, Ahmad Pradipta Budhihatma; Rofii, Muhammad Syaroni, Mr. (UI Scholars Hub, 2021)
This study aims to review the interpersonal relations between the United States, China, and the European Union in terms of economics and security. Through qualitative methods using an interpersonal relations approach, this study shows the forms and diplomatic steps of the three countries. The results of this study indicate that the relationship between the United States, China, and the European Union actually has an imbalance, where the strengths of each country are very different from one another. This is reflected in their different roles in international politics. The United States maintains significant strategic and political alliances around the world, including in Europe and East Asia. The European Union only has power within Europe, and it cannot project significant military power into East Asia. While China has significant military capabilities in East Asia and competes with the United States in the regional balance of power, global military power is still unable to compete. Keywords: interpersonal relations, economy, security, United States-European Union-China